The influence of anaesthesia on diffuse noxious inhibitory controls in the rat - White, Kate (2021)
In healthy animals and humans, a test stimulus will attenuate to a noxious conditioning stimulus applied elsewhere on the body; a phenomenon termed diffuse noxious inhibitory controls (DNIC). This endogenous pain inhibitory system can be used to study impairments in descending pain modulation, which may underlie some chronic pain conditions. The descending modulation and spinal nociceptive processing can be studied in anaesthetised rodents by examining nociceptive withdrawal reflexes (NWR) which are nocifensive, polysynaptic, multisegmental spinal reflexes designed to withdraw a limb from a damaging insult. These reflexes can be studied by measuring the electromyographic activity in limb muscles. Refining the anaesthetic for studying the NWR paradigm was the first aim of the study. The ideal anaesthetic for nociceptive studies will provide immobility, unconsciousness and be devoid of cumulative and antinociceptive effects. The pharmacokinetics and pharmacodynamics (PK/PD) of the anaesthetic agent alfaxalone were determined in male and female Sprague Dawley rats. These data informed subsequent DNIC studies. Nitrous oxide is also used commonly as a component of anaesthesia in animals and humans and has been used in laboratory rodent experiments for decades. In view of this, parsing out the modulating effects of N2O on an NWR model in naïve animals was undertaken to determine whether preconditioning with N2O could influence descending controls and DNIC. Experiments were performed in naïve Sprague Dawley rats with an intact neuraxis and rats decerebrated at the pre-collicular level to evaluate the suprapsinal contribution. Lewis rats resistant to N2O antinociceptive effects were also studied. N2O preconditioning had a significant effect on the level of DNIC which differed depending on the reflex studied. Lewis rats were resistant to N2O’s effects on DNIC. The final series of experiments evaluated preconditioning with N2O on DNIC in an induced osteoarthritis model demonstrating differences in the magnitude of DNIC between the controls and diseased animals albeit reflex specific differences. In conclusion based on these results it would be advisable to omit N2O from anaesthesia protocols interrogating the descending control of reflexes in rats. It is evident that N2O is able to modulate descending controls and further work is required to investigate the translational possibilities of this intervention.